The Crucial Role of Personal Values on Well-Being and Resilience in the Software Industry - Yurum, Ozan Rasit; Ozcan-Top, Ozden (Ieee Computer Soc, 2024)
Personal values play a pivotal role in shaping individuals' behaviors and decisions. This research aims to determine how alignment with personal values in both professional and personal life influences an individual's resilience and well-being in the software industry.
Keywords: Software; Resilience; Surveys; Interviews; Correlation; Software reliability; Security